2011
DOI: 10.1183/09031936.00024910
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary drug administration in neonatal and paediatric critical care: a comprehensive review

Abstract: Administration of drugs directly into the respiratory tree first was proposed a long time ago. Surfactant is the paradigmatic example of such therapies. Many other drugs have been used in the same way and further compounds are under investigation for this aim. In the last two decades, despite the wide number of drugs available for direct lung administration in critical care patients, few controlled data exist regarding their use in neonates and infants.This review will focus on drugs clinically available in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 168 publications
(167 reference statements)
0
23
0
1
Order By: Relevance
“…This meant testing BD against the most stringent conditions (i.e., the most relevant age range with distinct characteristics). This adds significantly to the relevance of the data, as these peculiarities lead to differences in terms of epidemiology, prognosis, ventilatory modalities [7], efficacy of surfactant [15,22], and ancillary therapies [23], as well.…”
Section: Discussionmentioning
confidence: 99%
“…This meant testing BD against the most stringent conditions (i.e., the most relevant age range with distinct characteristics). This adds significantly to the relevance of the data, as these peculiarities lead to differences in terms of epidemiology, prognosis, ventilatory modalities [7], efficacy of surfactant [15,22], and ancillary therapies [23], as well.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that treatment of cold blooded lizards with leptin, a product of adipocytes, increases their body temperature [83]. These synergistic selection pressures for adipogenesis would have been further functionally enhanced by the coordinate physiologic effects of epinephrine on the heart [84], lung [85], and fat depots [86], underpinned structurally by the increased production of leptin by fat cells, which is known to promote the formation of blood vessels [80] and bone [87], accommodating the infrastructural changes necessitated by the evolution of complex physiologic traits.…”
Section: Pparγ Mediates the Evolutionary History Of The Adipocytementioning
confidence: 99%
“…7,9 This route of administration, whose paradigmatic example is surfactant, is common in neonatal critical care and ensures a total bioavailability of the drug where it is needed. 42 Because neonatal respiratory diseases are characterized mainly by local injury, the intrapulmonary delivery of varespladib might be a preferred route of administration because it will provide enzyme-and tissue-specific anti-inflammatory action at the lung. In this sense, our model should represent the situation of BALF in the diseased alveoli.…”
Section: Discussionmentioning
confidence: 99%